E-learning myths - Andrés GARCÍA MANZANO (Ediciones Universidad de Salamanca, 2016)
In recent years numerous educational proposals have arisen about the application of the I.C.T. to almost all the teaching aspects, especially the platforms of e-learning the ones that more expectations are raising between the different administrations and not few professionals of the education. In the imaginary one of Internet, numerous concepts appear like ubiquity, self-learning, simulation, individualized management of the knowledge and interactiveness, that the on-line education has appropriated them until confirming a false educational paradigm in which the roles of teachers and students are relaxed and diluted, and finally they are interchangeable and, sometimes, without meaning. As we can see in this article, is a matter of groundless extrapolations that, in not few moments, they conduct to a series of false "myths" about the should be of education.